THE IMPLEMENTATION OF ARTICLE 127 OF LAW OF INDONESIA REPUBLIC NUMBER 35 2009 FOR JUDGE’S SENTENCE ABOUT REHABILITATION FOR DRUG ABUSE CRIME - Meiriantony Meiriantony (Muhammadiyah Law Review Journal, 2017)
The national police, as well as being the stronghold of law enforcement,  has such a duty of protection of human rights. The problem is precisely the police in carrying out law enforcement more violates Human Rights, both administrative and procedural violations, and violations of physical/violence. It occurs in the case of the light up to the case that the heavy procedural infringement. The violation of human rights by police as if  become habit. Therefore, reinterpret human rights and human rights violations are understood by Police, is an attempt to answer the problem. Prevention of human rights violations requires such a cognitive approach. Placing mindset (thought) in the cognitive structure of apparatus as subject to change. The understanding of the criminal law and human rights instruments as knowledge and new awareness. Starting from the mental activity of apparatus for directing and controlling the mind for all the good things and open to do as well as close the negative things and not commendable. The police who realized that they have evidence of the important position that are empowered to enforce the law will give justice to man with wisdom and tact.